HAM Sebagai Superior Norms Dalam Pembatasan Hak Veto Anggota Tetap Dewan Keamanan PBB - Freidelino P.R.A. de Sousa; Rima Saputri (Universitas Medan Area, 2026)
This study aims to provide a normative justification for limiting the use of the veto power by the permanent members of the United Nations Security Council based on human rights as superior norms in international law. The veto power, as enshrined in Article 27(3) of the UN Charter, grants privileged authority to The Five permanent members to block draft Security Council resolutions. In practice, this power has been exercised to reject resolutions that even seek to address the protection of human rights. The absence of clear normative constraints on the exercise of the veto has consequently generated fundamental legal tensions when such authority conflicts with the protection of human rights. Accordingly, this study advances the argument that human rights norms, as hierarchically superior norms within international law, must operate as a normative basis for restricting the legitimacy of veto usage in the practice of the Security Council. This research adopts a normative legal methodology employing a conceptual approach, examining the relevant legal concepts of human rights and veto power within the framework of international law.